Sex differences in aortic augmentation index in adolescents. Issue 10 (October 2017) - Barraclough, Jennifer Y.; Garden, Frances L.; Toelle, Brett; O'Meagher, Shamus; Marks, Guy B.; Cowell, Christopher T.; Celermajer, David S.; Ayer, Julian G.
Abstract : Background: Augmentation index (AIx) is a noninvasive measure of pulse wave reflection. AIx is associated with cardiovascular disease. Adult women have a higher AIx than men, but the factors determining this sex-related difference remain to be determined. Methods: To examine factors associated with AIx in adolescents, participants in the Childhood Asthma Prevention Study, followed from birth, were assessed at age 14 years, with AIx standardized to a heart rate of 75/min (AIx_75) and pulse wave velocity. Associations of AIx_75 and pulse wave velocity with height, change in height, and measures of puberty were assessed. Results: AIx_75 was higher in women compared to men [−24.5 (12.1) versus −32.3 (12.4)%; P  < 0.001]. Lower AIx_75 was significantly related to greater change in height between 8 and 14 years, but not to achieved height. The sex difference in AIx was not independently related to puberty variables. Differences between sexes included early life weight gain, lipids, height, BMI–Z-score, change in height from 8 to 14 years, and age at peak height velocity. Change in AIx_75 from 8 to 14 years was highly associated with change in height (m) from 8 to 14 years (B = −88.8, 95% confidence interval −137.3 to −40.3, P  =  < 0.001). The difference between sexes established at 8 years was not amplified from 8 to 14 years. Conclusion: AIx is higher in girls than boys at 14 years and is closely associated with change in height between 8 and 14 years. Measures of puberty do not appear to independently influence the sex difference in AIx in adolescents. Abstract : Supplemental Digital Content is available in the text